PENGARUH KEMANDIRIAN BELAJAR TERHADAP PRESTASI MAHASISWA PADA PEMBELAJARAN E-LEARNING BERBANTUAN MODUL - ADI CANDRA KUSUMA; Arif Rakhman; Dani Fitria Brilianti (STKIP Andi Matappa, 2020)
The existence of work from home policy in learning encourages students to increase learning independence in the Covid 19 pandemic, online lectures applied by the campus require students to study independently so that the achievements obtained by students are not declining, so there is a need for suitable learning methods, one of them is E-learning module-assisted learning. The study aims to determine the effect of learning independence on student achievement in module-assisted E-learning learning. This type of quantitative research using Random Sampling, obtained a number of 182 research subjects even semester students in the academic year 2019/2020 on linear Algebra & Matrix sub-topics Linear Equation System. Data collection techniques using a questionnaire (questionnaire), tests and interviews. Data analysis using SPSS 2.2 application by testing the validity, reliability, normality, and regression. The results obtained by the magnitude of the effect of learning independence on student achievement in module-assisted E-learning by 73.4% and 26.6% are influenced by other factors with the regression equation Y = 8.863 + 0.426X. Students who passed KKM were 141 students (77%). Aspects of learning independence obtained motivation (28%), responsibility (25%), initiative (23%) and confidence (24%). From the results of the regression, the influence of learning independence on student achievement so that students are able to face obstacles in the conditions of distance learning by monitoring lecturers.